Composition of Aqueous-Saline Extracts of Cryopreserved Pig Organ Fragments - Galchenko, S. E. (Problems of Cryobiology and Cryomedicine, 2004)
The author studied the effect of cryopreservation regimes of pig organ fragments and the conditions of obtaining extracts on their composition. It was shown that during obtaining the water-saline extracts the release of biologically active substances into solution was higher in the case of cryopreserved fragments than of native ones. The release of peptides was higher in the case of fragments cryopreserved with PEO-1500. The optimal time of incubation was 60 min.